New Windows version of the AUDIX system for objective hearing assessments - Torres, Alejandro; Pérez, María Cecilia; de Armas, Jorge Luis; Eimil, Eduardo; Savío, Guillermo; Muxo, Vanesa; Martín, Vivian (Auditio, 2021)
he present work describes a new version of the AUDIX system, designed as a computerized workstation, for objective and subjective audiometry. The system is made up of a computer (PC) with a series of computer programs (“software”) which is connected through a universal interface (universal serial bus USB) with a specialized electronic block (“hardware”). The electronic block has two bioelectric amplifiers and a fully programmable digital acoustic stimulator with two independent channels. This allows both ears to simultaneously generate different complex stimuli (mixture of amplitude modulated tones). Acoustic stimuli can be presented through audiophones (supra-ear or insert), bone vibrator and / or speakers. The software programmed on a Windows platform has 5 different modules for the acquisition and analysis of transient (ABR) and steady state (ASSR) evoked potentials, behavioral audiometry, database administration and calibration. The system database allows you to store, delete, extract, create and make backup copies. During the acquisition of the auditory evoked potentials (AEP), different statistical methods are used as indicators for the objective detection of the responses. Baseline bioelectric activity (EEG monitoring) and averaging result (AEP) can be concurrently visualized. The results of the electroaudiometric examination are analyzed offline in a flexible way, generating multiple graphical reports and allowing automatic comparison with normative data. In the case of ASSR, the results can be presented in the standard format of a conventional audiogram using different scales (dB: HL, SPL, nHL). The AUDIX system has been widely validated in clinical practice, proving useful for the early detection of hearing loss and the accurate characterization of hearing across the entire range of audible frequencies.